Treatment of Wine Distillery Wastewater: A Review with Emphasis on Anaerobic Membrane Reactors - Melamane, X.L.; Strong, P.J.; Burgess, J.E. (South African Journal of Enology and Viticulture, 2016)
This review summarises research efforts and case studies in the treatment of wine distillery wastewaters. Experiences in treating wine distillery wastewaters can contribute to the field of oenology, as many oenologists are concerned with the selection, efficiency and economy of their wastewaters. Characteristics of wastewaters from different distilleries and various methods for treating these wastes are discussed. Wine distillery wastewaters are strongly acidic, have a high chemical oxygen demand, high polyphenol content and are highly variable. Primary attention is focused on the sustainable biological treatment of wine distillery wastewaters, mainly by energyefficient anaerobic digestion in different reactor configurations from bench to pilot and full-scale treatment. Finally, areas where further research and attention are required are identified.